2014
DOI: 10.1088/2053-1591/1/1/016302
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline indium films in the percolation threshold regime: time correlation between electric conduction and optical properties with film morphology

Abstract: Temperature-and hydrogen-induced changes in the optical properties of Pd capped V thin films D E Azofeifa, N Clark, W E Vargas et al.-Collective response of silver islands on a dielectric substrate W E Vargas, D E Azofeifa, N Clark et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The large particles are flattened which means that the polarization parallel to the plane of the substrate tends to be null, and they produce a shadow effect over the nano-sized ones. In the case of indium, it has been shown that the coexistence of close-packed submicron-sized particles, with nano-sized ones between them, forming thin films has significant effect in their optical properties [59], with a non negligible component of reflected diffuse radiation. The large particles in the L-film are dispersed which means that a small fraction of diffuse reflection should be expected.…”
Section: Dielectric Function Of a Thin Pd Film At Rtmentioning
confidence: 99%
“…The large particles are flattened which means that the polarization parallel to the plane of the substrate tends to be null, and they produce a shadow effect over the nano-sized ones. In the case of indium, it has been shown that the coexistence of close-packed submicron-sized particles, with nano-sized ones between them, forming thin films has significant effect in their optical properties [59], with a non negligible component of reflected diffuse radiation. The large particles in the L-film are dispersed which means that a small fraction of diffuse reflection should be expected.…”
Section: Dielectric Function Of a Thin Pd Film At Rtmentioning
confidence: 99%
“…A shutter near the QCM surface (see figure 1) allows us to immediately stop the interaction between the beam of atoms and the QCM. In order to avoid any environmental contamination, the system is mounted inside a high vacuum apparatus modified from that of [21] with the capacity to maintain pressures in the range of roughly 10 −7 Torr (10 −5 Pa). The pressure is constantly monitored by a pressure gauge model 354 MICRO-ION and kept stable in the order of 10 −7 Torr (10 −5 Pa) during all measurements reported below.…”
Section: Methodsmentioning
confidence: 99%